Temporal profiling of plasma cytokines, chemokines and growth factors from mild, severe and fatal COVID-19 patients (2020)
Dear Editor, In December 2019, a novel coronavirus that is related to severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) in phylogenetic distance was identified.1 This virus, which was later designated as SARS-CoV-2, also causes acute respiratory disease syndrome (ARDS) termed coronavirus disease 2019 (COVID-19), which was declared as a pandemic by the World Health Organization in March 2020.